2013
DOI: 10.1182/blood-2012-06-436782
|View full text |Cite
|
Sign up to set email alerts
|

Cooperating gene mutations in childhood acute myeloid leukemia with special reference on mutations of ASXL1, TET2, IDH1, IDH2, and DNMT3A

Abstract: Key Points• A comprehensive study of 19 gene mutations and their cooperation, including the first report of ASXL1 and TET2 mutations in pediatric AML.• The development of pediatric AML requires fewer gene mutations than adult AML.Gene mutations involving epigenetic regulators recently have been described in adult acute myeloid leukemia (AML). Similar studies are limited in children. We analyzed gene mutations and cooperation in pediatric AML with special reference on mutated epigenetic regulators. Nineteen gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 49 publications
2
90
0
1
Order By: Relevance
“…9,[18][19][20]24,25 In general, ASXL1 mutations are also rare in pediatric AML. 26,27 However, this was not seen in GATA2 deficiency patients. The average age of GATA2 deficiency patients with an ASXL1 mutation (35.8 ± 12.8 years old, range, 17-59 years old) was markedly younger than that of other MDS/AML groups, but not significantly different from that of GATA2 deficiency patients without an ASXL1 mutation (34.5±17.0 years old, range 10-78 years old) (ttest, P=0.81) ( Figure 2B).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 67%
“…9,[18][19][20]24,25 In general, ASXL1 mutations are also rare in pediatric AML. 26,27 However, this was not seen in GATA2 deficiency patients. The average age of GATA2 deficiency patients with an ASXL1 mutation (35.8 ± 12.8 years old, range, 17-59 years old) was markedly younger than that of other MDS/AML groups, but not significantly different from that of GATA2 deficiency patients without an ASXL1 mutation (34.5±17.0 years old, range 10-78 years old) (ttest, P=0.81) ( Figure 2B).…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 67%
“…19 The mutational status of IDH1/2 in 71 of the 168 patients had been reported before. 13 TET2/IDH mutated cases were measured both at diagnosis of MDS and on progression to sAML by pyrosequencing and/or deep sequencing of the relevant mutant alleles.…”
Section: Analysis Of Gene Mutationsmentioning
confidence: 99%
“…89 Although previous studies clearly pointed to an oncogenic role of DNMT3A in cancer, the recent discovery of genetic mutations of DNMT3A in acute myeloid leukemia (AML) suggested that its role in cancers may be more complex than was previously believed. [11][12][13][14][15][16][17][18][19][20][21][22][23] These highly recurrent DNMT3A mutations were closely associated with poor outcome in patients with AML. However, the functional implications of these mutations are still poorly understood.…”
Section: The Dual Roles Of Dnmt3a In Cancermentioning
confidence: 99%
“…10 However, several inactivating mutations of DNMT3A in myeloid malignancies [11][12][13][14][15][16][17][18][19][20][21][22][23] and loss of DNMT3A activity at advanced tumor stages 24 were recently identified. In addition, novel roles of DNMT3A in the hematopoiesis system 25 and in the age-related decline of cognition 26 have been revealed.…”
Section: Introductionmentioning
confidence: 99%